A NARRATIVE REVIEW OF PATHOGENESIS OF GESTATIONAL DIABETES MELLITUS. - Shankar, Dr Anand (Student’s Journal of Health Research Africa, 2023)
Gestational Diabetes Mellitus (GDM) is characterized by impaired glucose metabolism that initially becomes evident during gestation. This narrative review provides a comprehensive overview of various aspects of the pathogenesis of GDM, shedding light on its risk factors, genetic factors, and implications for postpartum health. Extensive epidemiological research has revealed a correlation between increasing environmental temperatures and a heightened risk of GDM, often associated with diminished β-cell function. Key elements contributing to the development of GDM include β-cell dysfunction and insulin resistance in bodily tissues. Genetic investigations have pinpointed common genetic variations as culprits for both GDM and T2DM. Women who experience GDM face an elevated possibility of emerging T2DM in later periods of life. Additionally, those with a past of GDM are 7 times more prone to postpartum diabetes than individuals without such a history. Various factors, such as maternal age, pregnancy-related glucose conc., family medical history, pre-gestation and postpartum BMI, dietary habits, bodily movement, and breastfeeding, have been identified as risk variables for postpartum diabetes among females with GDM. Furthermore, females with GDM have an amplified susceptibility to conditions like pre-eclampsia or eclampsia during pregnancy, rendering them more at risk for cardiovascular diseases. Consequently, the management of GDM is primarily aimed at mitigating difficulties for both the mother and the fetus, maintaining optimal glycemic levels, and preventing excessive weight gain. Future research should focus on further understanding the pathogenesis of GDM, identifying modifiable risk factors, and developing effective interventions. In clinical practice, managing GDM involves maintaining optimal glycemic levels, preventing excessive weight gain, and implementing lifestyle changes such as therapeutic measures, exercise, dietary modifications, and low-glycemic-index diets to mitigate post-meal hyperglycemia and reduce insulin resistance. Addressing GDM effectively is crucial for the well-being of both mothers and their babies.